2021
DOI: 10.1002/sim.8886
|View full text |Cite
|
Sign up to set email alerts
|

Early completion of phase I cancer clinical trials with Bayesian optimal interval design

Abstract: Phase I cancer clinical trials have been proposed novel designs such as algorithm‐based, model‐based, and model‐assisted designs. Model‐based and model‐assisted designs have a higher identification rate of maximum tolerated dose (MTD) than algorithm‐based designs, but are limited by the fact that the sample size is fixed. Hence, it would be very attractive to estimate the MTD with sufficient accuracy and complete the trial early. O'Quigley proposed the early completion of a trial with the continual reassessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In conclusion, Bayesian optimal design addresses a fundamental problem in science: the intelligent collection of data resulting in greater information efficiency, reduced sampling cost and improved estimation. Such benefits have been observed in clinical trials [19][20][21][22] and environmental monitoring [15,23], and we have shown how they can be used to offer flexible yet efficient sampling in a real-world context. One limitation of the approach is the potential reliance of designs on a number of assumptions, e.g.…”
Section: (B) Case Study: Sampling Windows For Coral Reef Monitoringmentioning
confidence: 70%
“…In conclusion, Bayesian optimal design addresses a fundamental problem in science: the intelligent collection of data resulting in greater information efficiency, reduced sampling cost and improved estimation. Such benefits have been observed in clinical trials [19][20][21][22] and environmental monitoring [15,23], and we have shown how they can be used to offer flexible yet efficient sampling in a real-world context. One limitation of the approach is the potential reliance of designs on a number of assumptions, e.g.…”
Section: (B) Case Study: Sampling Windows For Coral Reef Monitoringmentioning
confidence: 70%
“…Although the BOIN and Keyboard designs have a stopping rule that can be used to terminate the trial if the number of patients treated exceeds the predetermined number, there is no statistical basis for the predetermined number. Kojima [35][36][37] proposed an early completion method for model-assisted designs but did not discuss the applicability of this method for dose combination trials.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study cannot identify the MTD until the number of patients treated reaches the sample size. Early identification methods for MTD have been proposed [ 4 , 5 ]. However, the methods cannot apply to TITE model-assisted designs.…”
Section: Introductionmentioning
confidence: 99%